Host plant resistance to podfly (Melanagromyza obtusa) in pigeon pea (Cajanus cajan) - LAL, S S; RATHORE, Y S (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conductcd under field condition during 1999-91, 1992-93 and 1993-94 to evaluate 2 033 accessions of medium 01’ late-maturity group of pigeonpea [Cajanus cajan (L.) Millsp.]. Each entry was sown in paired rows in augmented design with local checks ’Bahar’ and ’T 7’. Entries were evaluated on the basis of pod damage (%) and relative resistance rating. Selection ’PDA 88-2E’, ’PDA 89-2E" ’PDA 92-1E’, ’PDA 92-2E’, ’PDA 92-3E’,’PDA 93-1 E’, ’SL 21-1-3’, ’SL 21-6-2’, ’SL 21-9-2’ and ’SL 22-2-3’ were found quite promising against podfly (Melanagromyza obfusa Malloch) in station and multilocation testing. These lines can be used as donors in resistance breeding programme and can also be selectively used for cultivation in podfly-endemic areas awaiting a suitable replacement by a prominent variety.